CLINICAL CHARACTERISTICS, IMAGING, AND SURGICAL OUTCOMES OF CHRONIC SUBDURAL HEMATOMA AT LONG KHANH REGIONAL GENERAL HOSPITAL FROM 2021 TO 2024 - Ngọc Bun, Đặng; Nhật Thành, Phạm; Phước Đoàn, Bùi (Journal of Health and Aging, 2026)
Chronic subdural hematoma (CSDH) is a common condition in the elderly, often associated with a prior history of trauma and progressively worsening symptoms if not diagnosed and treated promptly. This study aims to describe the clinical characteristics, imaging findings, and surgical outcomes of patients with CSDH treated at Long Khanh Regional General Hospital from 2021 to 2024; A total of 34 patients diagnosed with CSDH underwent single-burr-hole surgical drainage between January 2021 and September 2024. The mean patient age was 68.4 ± 16.9 years, with males accounting for 88.2%. Trauma was the primary cause (52.9%), including falls in 29.4% of cases. Motor weakness was the most common symptom (64.7%), followed by headache (55.8%), altered consciousness (23.5%), and aphasia (20.6%). Most patients presented with mild traumatic brain injury (GCS 13–15, 76.5%), while coma was recorded in 8.8%. CT imaging showed a mean hematoma thickness of 21.1 ± 6.3 mm and a mean midline shift of 9.4 ± 4.8 mm; unilateral CSDH was observed in 70.6% of cases. All patients underwent single-burr-hole surgery. Postoperatively, 88.2% achieved a GCS of 15. There were no cases of infection or intraoperative bleeding. Recurrence occurred in four patients, including one requiring reoperation after three weeks; the mortality rate was 2.9%. The average hospital stay was 10.7 ± 5.4 days. At discharge, 73.5% of patients had good outcomes, and 73.5% returned to normal life within one month. In conclusion, single-burr-hole drainage for chronic subdural hematoma is effective, safe, and associated with favorable outcomes, low complication rates, and good functional recovery in most patients.